2016
DOI: 10.3892/or.2016.5105
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA-SNHG7 promotes the proliferation, migration and invasion and inhibits apoptosis of lung cancer cells by enhancing the FAIM2 expression

Abstract: There is growing evidence that long non-coding RNAs (lncRNAs) are related to cancer development. In the present study, we found that the expression levels of lncRNA-SNHG7 mRNA and protein obviously increased in lung cancer tissues compared to adjacent non-cancerous tissues. Simultaneously, the expression levels of Fas apoptotic inhibitory molecule 2 (FAIM2) also increased in lung cancer tissues. In addition, lncRNA-SNHG7 was of positive relevance with FAIM2 in human lung cancer tissues. Silence of lncRNA‑SNHG7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 42 publications
1
74
0
Order By: Relevance
“…The high expression of lnc-HOTAIR can promote the proliferation, migration and invasion of tumor cells, while the unlimited proliferation of cells is closely related to the occurrence and development of cancer [50]. LncRNA-SNHG7 promotes the proliferation of lung cancer cells by enhancing the FAIM2 expression [51]. Our results indicated lncRNA-OBFC2A affected cell proliferation by regulating the expression of proliferation-related genes in AHH-1 cells.…”
Section: Discussionmentioning
confidence: 87%
“…The high expression of lnc-HOTAIR can promote the proliferation, migration and invasion of tumor cells, while the unlimited proliferation of cells is closely related to the occurrence and development of cancer [50]. LncRNA-SNHG7 promotes the proliferation of lung cancer cells by enhancing the FAIM2 expression [51]. Our results indicated lncRNA-OBFC2A affected cell proliferation by regulating the expression of proliferation-related genes in AHH-1 cells.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies reveal that PVT1 is overexpressed in multiple cancers and correlated with cancer progression, including colorectal cancer , gastric cancer , and cervical cancer . In addition, a recent study showed that SNHG7 overexpression promotes cell migration and invasion in lung cancer by enhancing the FAIM2 expression . Here, we firstly analyzed PVT1 and SNHG7 expression levels in HCC cell lines using CCLE data , and the results showed that HuH1 cell has highest PVT1 and SNHG7 expression levels (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…It has been proven in extensive researches on cancers that the differentially expressed lncRNA pattern was obviously associated with the pathogenesis of various malignant tumors3435. In our study, nine lncRNAs meta-signature were incorporated for integrated analysis through a series of data mining and calculation.…”
Section: Discussionmentioning
confidence: 99%